If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6h = 4 + -2h Solving -6h = 4 + -2h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '2h' to each side of the equation. -6h + 2h = 4 + -2h + 2h Combine like terms: -6h + 2h = -4h -4h = 4 + -2h + 2h Combine like terms: -2h + 2h = 0 -4h = 4 + 0 -4h = 4 Divide each side by '-4'. h = -1 Simplifying h = -1
| l^-3/4=.037 | | 5m+19-3m=-15+4m | | 8+5x=9+4x | | 3m^2/9 | | -4v-4=-6v-20 | | 3c+10=2c-3 | | 3x-60=21 | | x^-3/4=.037 | | w-7=9+5-2w | | -4y+1=1-6y-10 | | 3/8x-1/2=21/8 | | s(s/3/5)=-3/7 | | -24=5x-8x | | -6p-9=3p | | 2b+1=18 | | -7+4z=2z+7 | | y-2=-7/8(x-8) | | -7+4f=2z+7 | | -9-u=-4u | | -14+34=6x-56 | | 6x+12=-6x-17 | | Y=-3*(3*3)-1 | | 6x+12=6x-17 | | -3+7f=8f+4 | | -13+6y= | | -csc(3.14/4) | | 2sec^2=0 | | 4x+15=-9x-17 | | Y=-3*(-3*-3)-1 | | 2x-30=5x-10 | | 4(x+4)=4(x+9) | | tan^4x-5tan^2x+4=0 |